Literature Review: Bioactivity and Drug Formulation of Tapak Dara (Catharanthus roseus) - Fadhli, Haiyul; Fadillah, Ma’isyatul; Hazimah, Hazimah; Fitriah, Dina (Faculty of Pharmacy, Widya Mandala Surabaya Catholic University, Indonesia, 2024)
Tapak dara (Catharanthus roseus), also known as Madagascar periwinkle or Vinca, is a tropical plant native to Madagascar and has been widely distributed throughout the world, including in Indonesia. This review article looks at bioactivities and drug formulations using different parts of the Catharanthus roseus plant. Literature sources and data were collected through Google Scholar and Google Books on the topic of formulations and pharmacological activities of Catharanthus roseus, published from 2014 to 2024. This review describes various studies showing the potential of Catharanthus roseus plants in various bioactivities such as antioxidants, anticancer, analgesic, antihyperglycemic, antibacterial, wound healing, anti-inflammatory, hepatoprotective, antihyperlipidemic, and antidiabetic properties. Besides bioactivity aspects, this review also covers formulations involving Catharanthus roseus, including the development of various products such as extracts, ointments, creams, gels, emulgels, and nano emulsions for medical purposes. In conclusion, this article provides an in-depth insight into the bioactivity of the Catharanthus roseus plant and its potential in drug formulations.